2004
DOI: 10.1002/pssc.200405366
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐induced optical phonon self‐energy changes in rhenium metal

Abstract: The effect of pressure on the temperature dependence of the E 2g optical phonon self-energy in rhenium has been investigated by Raman spectroscopy. Temperature-dependent mode Grüneisen parameters are determined. A comparison with numerical simulations of the temperature dependences of the phonon frequencies and line widths indicates pronounced changes in the electron band structure near the Fermi level under pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Anharmonic effects are usually modeled by three-and four-phonon decay processes [49][50][51] where a dominance of four-phonon processes can lead to phonon hardening and increasing lifetimes. [52][53][54] A possible explanation of this finding is that due to anharmonic effects, the phonon dispersion relation evolves with temperature. [55] A second important finding presented in Figure 3b is that the A g (6) mode of pentacene changes its PO periodicity from 180° below 80 K to 90° above 150 K. This change is reversible with temperature and indicative of a profound change in the Raman tensor elements of this vibration.…”
Section: Doi: 101002/adma201908028mentioning
confidence: 99%
See 1 more Smart Citation
“…Anharmonic effects are usually modeled by three-and four-phonon decay processes [49][50][51] where a dominance of four-phonon processes can lead to phonon hardening and increasing lifetimes. [52][53][54] A possible explanation of this finding is that due to anharmonic effects, the phonon dispersion relation evolves with temperature. [55] A second important finding presented in Figure 3b is that the A g (6) mode of pentacene changes its PO periodicity from 180° below 80 K to 90° above 150 K. This change is reversible with temperature and indicative of a profound change in the Raman tensor elements of this vibration.…”
Section: Doi: 101002/adma201908028mentioning
confidence: 99%
“…Importantly, strong anharmonicity does not necessarily lead to mode softening and decreasing phonon lifetimes. Anharmonic effects are usually modeled by three‐ and four‐phonon decay processes where a dominance of four‐phonon processes can lead to phonon hardening and increasing lifetimes . A possible explanation of this finding is that due to anharmonic effects, the phonon dispersion relation evolves with temperature …”
mentioning
confidence: 99%
“…This provides an additional tool to study the electronic excitations responsible for anomalous dispersion effects. Experiments at pressures up to 15 GPa have shown that the volume changes contribute no more than 20%-30% to the temperature-induced hardening of the phonon frequencies in osmium and rhenium, 24,25 confirming the dominant role of the e-ph interaction. [26][27][28] An anomalous phonon hardening in osmium has been found at pressures higher than 15 GPa under nonhydrostatic conditions.…”
Section: Introductionmentioning
confidence: 88%
“…There, the coupling is indicated by an anomalous temperature behavior of the E 2g phonon linewidths. Along with this anomaly, the phonon frequencies showed a typical softening upon cooling [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%